Synthesis of naturally-derived macromolecules through simplified electrochemically mediated ATRP - Chmielarz, Paweł; Pacześniak, Tomasz; Rydel-Ciszek, Katarzyna; Zaborniak, Izabela; Biedka, Paulina; Sobkowiak, Andrzej (Beilstein Journal of Organic Chemistry, 2017)
The flavonoid-based macroinitiator was received for the first time by the transesterification reaction of quercetin with 2-bromoisobutyryl bromide. In accordance with the “grafting from” strategy, a naturally-occurring star-like polymer with a polar 3,3',4',5,6-pentahydroxyflavone core and hydrophobic poly(tert-butyl acrylate) (PtBA) side arms was synthesized via a simplified electrochemically mediated ATRP (seATRP), utilizing only 78 ppm by weight (wt) of a catalytic CuII complex. To demonstrate the possibility of temporal control, seATRP was carried out utilizing a multiple-step potential electrolysis. The rate of the polymerizations was well-controlled by applying optimal potential values during preparative electrolysis to prevent the possibility of intermolecular coupling of the growing polymer arms. This appears to be the first report using on-demand seATRP for the synthesis of QC-(PtBA-Br)5 pseudo-star polymers. The naturally-derived macromolecules showed narrow MWDs (Đ = 1.08–1.11). 1H NMR spectral results confirm the formation of quercetin-based polymers. These new flavonoid-based polymer materials may find applications as antifouling coatings and drug delivery systems.
Keywords: flavonoids; on-demand seATRP; quercetin-based macromolecules